Studying the effect of seaweed extract on some growth characteristics of mung beans grown hydroponically - Sajad fuad kadhem Mutair; Rusul laith Abd Alabas Abd Allah; Safa khalaf hussein aldulamy; Shahad Abdulazez khdher abass; Zahraa Saad Hassn Ali (Genius Journals, 2024)
The article is devoted to the role of operational-investigative activities in the customs authorities in identifying and suppressing crimes in the field of customs activities, as well as issues of the effective waysof its organization.
Keywords: Operational-investigative activity; customs crimes; crimes in the field of customs activities